Numerical Simulation of the Performance Characteristics of the Hybrid Closed Circuit Cooling Tower - Sarker, M. M. A. M. A.; Kim, E.; Moon, G. C. C.; Yoon, J. I. I. (Nonlinear Analysis: Modelling and Control, 2008)
The performance characteristics of the Hybrid Closed Circuit Cooling Tower (HCCCT) have been investigated applying computational fluid dynamics (CFD). Widely reported CFD techniques are applied to simulate the air-water two phase flow inside the HCCCT. The pressure drop and the cooling capacity were investigated from several perspectives. Three different transverse pitches were tested and found that a pitch of 45 mm had lower pressure drop. The CFD simulation indicated that when air is supplied from the side wall of the HCCCT, the pressure drop can be over predicted and the cooling capacity can be under predicted mainly due to the non-uniform air flow distribution across the coil bank. The cooling capacity in wet mode have been calculated with respect to wet-bulb temperature (WBT) and cooling water to air mass flow rates for different spray water volume flow rates and the results were compared to the experimental measurement and found to conform well for the air supply from the bottom end. The differences of the cooling capacity and pressure drop in between the CFD simulation and experimental measurement in hybrid mode were less than 5 % and 7 % respectively for the uniform air flow distribution.